Feel Good Incorporated: Using Positively Framed Feedback in Library Instruction Course Evaluations Using a Survivorship-Bias Lens - Aldred, Benjamin Grantham (Evidence Based Library and Information Practice, 2025)
Objective – This research project makes use of a large dataset of directly solicited positively framed student feedback on virtual library instruction in order to 1. Identify potential improvements to instructional instrument, and 2. Create method for using positively framed student feedback for instructional improvement.Methods – Research team used content analysis to tag student responses using a rubric based on learning objectives and structure of instructional instrument. Tags were analyzed to identify patterns and categorize student-identified research skills.Results – An interpretive lens based on concepts from survivorship bias was used to highlight frequency differences between student identified skills and learning objectives. Gaps were identified between expected range of outcomes and actual range of outcomes, highlighting potential areas of instructional instrument that could be improved or given greater emphasis to ensure retention.Conclusion – A survivorship bias lens combined with a large dataset and a structured set of learning outcomes can make directly solicited positively framed feedback into a tool for instructional improvement.